Experimental Study of Self Compacting RC Slabs with Opening Strengthening with Carbon Fiber Laminated and Steel Fiber - Jasim Muhammed, Nura (Journal of Engineering and Sustainable Development, 2012)
Introducing openings in existing reinforced concrete slabs can severely weaken the slabs due to the cut-out of both concrete and reinforcing steel. There are several traditional approaches to strengthening slabs with openings; however. these approaches can be cumbersome, expensive, and may require significant usable floor area. This paper reports field tests on the use of Carbon Fiber Reinforced Polymers (CFRP) strengthening and steel fiber to restore the load capacity of the slab after having openings cut out in the positive moment region. Eight slabs (450*450*40) mm were cast to evaluate the ability of the CFRP strengthening and steel fiber to restore the load capacity of the slab, made of self-compacting concrete, after introducing the openings. Two different strengthening techniques were investigated to determine the most effective system for strengthening. The two different strengthening techniques are the use of externally bonded CFRP strips and adding steel fiber 1% by volume fraction. Test results showed that the two strengthening techniques increased the load-carrying capacities of the slabs with openings. The CFRP is more effective than the steel fiber technique. The use of CFRP enable the slabs to restore their full load capacity and increased it by 30%, also the steel fiber hence enabled the slab to restore its full capacity and increased it by 20 %.CFRP and steel fiber reduced the cracks at the inside faces of the opening and also CFRP prevents it at the inside corners.